Analisis Kesulitan Menyelesaikan Soal Higher Order Thinking Skill (HOTS) Materi Sistem Persamaan Linear Dua Variabel (SPLDV) Pada Siswa Kelas VIII SMP Negeri 34 Makassar - Sri Hardiyanti Amaliah; Baharullah Baharullah; Ma'rup Ma'rup (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2021)
Abstract               Sri Hardiyanti Amaliah A, 2021. Difficulty Analysis of Resolving Higher Order Thinking Skill (HOTS) Questions on Two-Variable Linear Equation System (SPLDV) in Class VIII Students of SMP Negeri 34 Makassar. Thesis. Mathematics Education Study Program, Teacher Training and Education Faculty, Muhammadiyah University of Makassar. Advisor I Dr. Baharullah., M.Pd. and Advisor II Ma'rup, S.Pd., M.Pd. The main problem in this research is how the description of the difficulty in solving Higher Order Thinking Skill questions about the two-variable linear equation system material in class VIII students of SMP Negeri 34 Makassar. This study aims to describe the difficulty of solving the Higher Order Thinking Skill questions of the two-variable linear equation system material for the eighth grade students of SMP Negeri 34 Makassar. This type of research is a qualitative descriptive study. This research procedure includes preparation, implementation and completion. The subjects in this study were 3 students of class VIII.A SMP Negeri 34 Makassar. The technique of determining the subject is by giving tests to all students of class VIII.A to select the 3 students who get the highest score from the test results. Determination of the subject based on the consideration of the subject teacher and test score results. This study refers to three indicators of the difficulty of HOTS questions, namely: analyzing, evaluating, and creating. The instrument in this study was a test of the difficulty of the Higher Order Thinking Skill questions and interview guidelines.               Based on the results of research which shows that S1 has difficulty conceptual and verbal. Where is the difficulty in separating important pieces of information and difficulty in writing conclusions at the stage of evaluating and creating. S2 experiences conceptual and verbal difficulties, where it is difficult to separate important pieces of information and difficulty in writing conclusions. S2 also has difficulty making correct hypotheses and difficulties in conducting tests in detail in the hypotheses it makes. S3 has difficulty in concept, principle and verbal at the stage of evaluating and creating, difficulty in making hypotheses of the problems being asked, difficulties in testing, difficulty in solving questions and is only able to work on questions in the evaluation stage halfway throughKeywords: Difficulty, SPLDV, Higher Order Thinking Skill AbstrakSri Hardiyanti Amaliah A, 2021. Analisis Kesulitan Menyelesaikan Soal Higher Order Thinking Skill (HOTS) Materi Sistem Persamaan Linear Dua Variabel (SPLDV) pada Siswa Kelas VIII SMP Negeri 34 Makassar. Skripsi. Program Studi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Makassar. Pembimbing I Dr. Baharullah., M.Pd. dan Pembimbing II Ma’rup, S.Pd., M.Pd. Masalah utama dalam penelitian ini yaitu bagaimana deskripsi kesulitan menyelesaikan soal Higher Order Thinking Skill materi sistem persamaan linear dua variabel pada siswa kelas VIII SMP Negeri 34 Makassar. Penelitian ini bertujuan untuk mendeskripsikan kesulitan menyelesaikan soal Higher Order Thinking Skill materi sistem persamaan linear dua variabel pada siswa kelas VIII SMP Negeri 34 Makassar. Jenis penelitian ini adalah penelitian deskripsi kualitatif. Prosedur penelitian ini meliputi persiapan, pelaksanaan dan penyelesaian. Subjek dalam penelitian ini adalah siswa kelas VIII.A SMP Negeri 34 Makassar sebanyak 3 orang siswa. Teknik penentuan subjek yaitu dengan memberikan tes kepada seluruh siswa kelas VIII.A untuk memilih 3 siswa yang memperoleh nilai tertinggi dari hasil tes. Penentuan subjek berdasarkan pertimbangan guru mata pelajaran dan skor hasil tes. Penelitian ini mengacu pada tiga indikator kesulitan soal HOTS yaitu: menganalisis, mengevaluasi, dan mencipta. Instrumen dalam penelitian ini adalah tes kesulitan soal Higher Order Thinking Skill dan pedoman wawancara. Berdasarkan hasil penelitian yang menunjukkan bahwa S1 mengalami kesulitan konsep dan verbal. Dimana kesulitan dalam memisahkan bagian-bagian informasi yang penting dan kesulitan dalam meuliskan kesimpulan pada tahap mengevalusi dan mencipta. S2 mengalami kesulitan konsep dan verbal, dimana kesulitan  memisahkan bagian-bagian informasi yang penting dan kesulitan dalam menuliskan kesimpulan. S2 juga kesulitan dalam membuat hipotesis yang benar dan kesulitan dalam melakukan pengujian dengan rinci dalam hipotesis yang dibuatnya. S3 mengalami kesulitan konsep, prinsip dan verbal pada tahap mengevaluasi dan mencipta, kesulitan dalam membuat hipotesis dari permasalahan yang ditanyakan, kesulitan dalam melakukan pengujian, kesulitan menyelesaikan soal dan hanya mampu mengerjakan soal tahap mengevaluasi dengan stengah perjalananKata kunci: Kesulitan, SPLDV, Higher Order Thinking Skill